Peningkatan Kualitas Biji Kakao melalui Fermentasi di Dusun Tamilo, Desa Saritani Kabupaten Boalemo, Provinsi Gorontalo - Mustamin Ibrahim; Jusna Ahmad; Charunnisah J. Lamangantjo (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
The low quality of cocoa beans in Tamilo Hamlet, Saritani Village, Boalemo Regency, is primarily caused by farmers' preference to sell wet and unfermented (asalan) beans due to urgent economic pressures and entrapment in the ijon system (pre-harvest lending). This community service program aims to improve cocoa bean quality through the implementation of fermentation techniques using the Participatory Action Research (PAR) approach, which positions farmers as active subjects of change. The implementation methodology was carried out sequentially, starting with an awareness and economic analysis phase to reconstruct farmers' mindsets, followed by a technology transfer phase through Field Schools covering cultivation training (Good Agricultural Practices/GAP) and processing (Good Manufacturing Practices/GMP). The results indicate a transformation in farmers' economic orientation from "quick cash" to "value-added" after farming simulations demonstrated that the price increase of fermented beans could offset weight shrinkage and increase profit margins. The technical success of the program is marked by the active participation of 15 farmers and the independent construction of 10 fermentation box units using local materials, indicating the self-reliance and sustainability of post-harvest technology adoption in the partner location.